Effects of targeting highly expressed in cancer protein 1 (Hec1) inhibitor INH 1 in breast cancer cell lines In Vitro: Targeting Hec1 in breast cancer cell lines - Topçul, Mehmet; Çetin, İdil (Cellular and Molecular Biology, 2023)
In the present study, the in vitro antiproliferative effect of targeting highly expressed cancer protein 1 (Hec1) inhibitor INH1 was investigated in estrogen receptor-positive MCF-7 cell line originating from an in situ carcinoma and triple negative MDA-MB-231 cell line originating from metastatic carcinoma. Cell viability, xCELLigence RTCA DP instrument CI values, MI, BrdU proliferation assay, and AI analyses were employed for this purpose. According to the findings of the current study, INH1 altered cell proliferation by lowering cell viability, CI, MI values, and BrdU proliferation while raising AI values in both cell lines. Between the experimental and control groups, there were noticeable changes (p<0.05). These findings imply that INH1’s mode of action is not dependent on the presence of estrogen receptors, making it a potentially effective therapy for breast cancer.